Characteristics of miRNA interaction with 5’UTR, CDS, 3’UTR mRNA candidate genes of breast cancer subtypes (Experimental biology, 2018)
Different subtypes of breast cancer are distinguished by a set of candidate genes involved in the development of this disease. The expression of many genes is regulated by binding of their mRNA with miRNA, therefore it is required to identify which candidate genes of oncogenesis and in what degree they can interact with miRNA. The purpose of this work was to establish the interaction characteristics of the known 3701 miRNAs with mRNA 92 candidate genes of breast cancer subtypes. 19 genes from 25 candidate genes of the her2 subtype were targets for miRNA. The binding sites of 67 miRNAs were located in 5’UTR, CDS, 3’UTR and the average free energy (ΔG) of miRNA binding with mRNA was   equal to -120,2 ± -7,6 kJ/mole, -123,6 ± -9,8 kJ/mole, -110,4 ± -9,8 kJ/mole, respectively. 31 miRNA associations with mRNA, having the free binding energy more than -120 kJ/mole are recommended for the diagnosis of the her2 subtype. 33 genes from 47 candidate genes of the triple-negative subtype were targets for miRNA. The binding sites of 90 miRNAs were located in 5’UTR, CDS, 3’UTR and the average ΔG value of miRNA binding with mRNA was equal to -123,5 ± -7,0 kJ/mole, -114,1 ± –7,9 kJ/mole,-106,9 ± –4,9 kJ/mole, respectively. 36 miRNA associations with mRNA are recommended for the diag- nosis of the triple-negative subtype. 14 genes from 20 candidate genes of luminal A and B subtypes were miRNA targets. The binding sites of 86 miRNAs were located in 5’UTR, CDS, 3’UTR and the average ΔG value of miRNA binding with mRNA was equal to -121.2 ± -9,5 kJ/mole, 120,4 ± -7,8 kJ/mole, -118,9± -8,1 kJ/mole, respectively. 51 miRNA associations with mRNA were recommended for diagnosis of luminal A and B subtypes. In the mRNA of many genes, sites containing two or more miRNA binding sites were identified with arranging of their nucleotide sequences, which reduces the proportion of bind- ing sites in the nucleotide composition in 5’UTR, CDS, and 3’UTR several times. Based on the obtained results, the groups of miRNA and mRNA associations of candidate genes are recommended to develop methods for diagnosis subtypes of breast cancer.Key words: miRNA, mRNA, subtypes of breast cancer, target genes.